Vitamin D, Thyroid Hormones and Cardiovascular Risk: Exploring the Components of This Novel Disease Triangle - Vassalle, Cristina; Parlanti, Alessandra; Pingitore, Alessandro; Berti, Sergio; Iervasi, Giorgio; Sabatino, Laura (Frontiers in Physiology, 2021)
The role of thyroid hormones in the cardiovascular (CV) system, through several direct and indirect effects is recognized. Even very small modification in thyroid hormone levels (as those observed in subclinical hypothyroidism or hyperthyroidism, and low triiodothyronine syndrome) may adversely affect the CV system, whereas thyroid hormones benefit the CV system and improve the prognosis. There is also evidence of vitamin D effects on cardiometabolic disease (e.g. through modulation of endothelial and smooth muscle cell activity, renin-angiotensin-aldosterone system, nitric oxide, oxidative stress, and inflammatory response), as well as an association between vitamin D [25(OH)D] deficiency and autoimmune thyroid diseases or cancer, and a relationship between vitamin D concentration and titers of antibodies and thyroid autoimmunity replacement. Interestingly, experimental data indicate a direct effect of vitamin D on Type 2 deiodinase expression causing subsequential peripheral conversion of T4 into T3. However, the functional links among thyroid hormones, vitamin D and the cardiovascular system, and clinical effects of coexisting abnormalities in this new troublesome triad, have not yet been reviewed. The main aim of this review is to discuss pathophysiology of this relationship, proposing new mechanistic insights involving vitamin D in the modulation of cardiometabolic disease and thyroid profile.